1997
DOI: 10.2527/1997.7592344x
|View full text |Cite
|
Sign up to set email alerts
|

Two-way selection for daily gain and feed conversion in a composite rabbit population.

Abstract: We conducted a two-way selection experiment in a composite rabbit population to investigate the responses to selection for postweaning ADG and feed conversion (FC). Two generations of crossing, followed by four generations of random pair matings, preceded three generations of selection. Selection was practiced within four lines: high-feed conversion (HFC), low-feed conversion (LFC), high gain (HG), and low gain (LG). Data on 1,446 rabbits from the random mating and selection generations were fitted to an anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
3
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 13 publications
(25 reference statements)
6
42
3
6
Order By: Relevance
“…For instance, post-weaning ADG was currently increased by nearly 1 g/d per generation of selection on 63-d body weight, versus 0.83 g/d for Rochambeau et al [34] and 0.45 g/d for Piles and Blasco [26] per generation by direct selection on postweaning ADG breeding values. In agreement with previous studies on rabbits selected for ADG [8,22], the lowest feed conversion ratio was observed in the rapid-growing animals, since the genetic correlation between ADG and market weight was high (r g = 0.82 to 0.91, current study, [22]). …”
Section: Symmetrical and Asymmetrical Responses For Selection On Bodysupporting
confidence: 93%
See 3 more Smart Citations
“…For instance, post-weaning ADG was currently increased by nearly 1 g/d per generation of selection on 63-d body weight, versus 0.83 g/d for Rochambeau et al [34] and 0.45 g/d for Piles and Blasco [26] per generation by direct selection on postweaning ADG breeding values. In agreement with previous studies on rabbits selected for ADG [8,22], the lowest feed conversion ratio was observed in the rapid-growing animals, since the genetic correlation between ADG and market weight was high (r g = 0.82 to 0.91, current study, [22]). …”
Section: Symmetrical and Asymmetrical Responses For Selection On Bodysupporting
confidence: 93%
“…Successful selection in rabbits was previously shown for ADG [4,22,35] and body weight at market age [18,34]. However, a higher genetic progress for body weights and ADG was obtained in the present work, mainly because of the efficiency of selection on BLUP breeding values in comparison with selection on phenotypic values.…”
Section: Symmetrical and Asymmetrical Responses For Selection On Bodymentioning
confidence: 59%
See 2 more Smart Citations
“…Esto es debido a que hoy en día los gastos de alimentación suponen el principal coste de producción (70-80% en conejo (Moura et al, 1997), por lo que la mejora de la eficiencia alimentaria tiene repercusión directa en el balance económico de la explotación.…”
Section: Introductionunclassified